Toraja Architectural Wisdom as a Catalyst for Contemporary Design Innovation - Andi Abidah; Andi Yusdy Dwiasta; Surianto B Mappangara; Ivan Fachrul Marsa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the architectural wisdom embedded in Toraja vernacular traditions and its potential to inspire culturally grounded contemporary design innovation. Using a qualitative interpretive approach that combines field observation, architectural documentation, and interviews with cultural experts, the research identifies the morphological, symbolic, and ecological principles that define the Tongkonan, the traditional Toraja house. The results show that Toraja architecture demonstrates advanced environmental adaptation through elevated timber structures, aerodynamic saddle-shaped roofs, and passive ventilation strategies. Equally significant is its symbolic spatial ordering, which reflects Toraja cosmology and kinship systems, revealing architecture as both a material and cultural construct. The study finds that these vernacular principles align strongly with contemporary design agendas related to sustainability, low-carbon construction, participatory design, and identity-driven architecture. Furthermore, the communal building practices associated with Tongkonan construction illuminate culturally embedded models of social collaboration that hold contemporary relevance. The findings suggest that when interpreted critically and respectfully, Toraja architectural wisdom can function as a catalyst for innovative design solutions that integrate tradition with modern needs. The study concludes that indigenous knowledge should not be viewed as static heritage but as an active resource for shaping contextually meaningful architectural futures. Keywords: Toraja architecture; vernacular wisdom; Tongkonan; contemporary design innovation; cultural sustainability